2013
DOI: 10.1002/ejoc.201300031
|View full text |Cite
|
Sign up to set email alerts
|

[2.2]Paracyclophane–Triazolyl Monophosphane Ligands: Synthesis and Their Copper and Palladium Complexes

Abstract: Triazole‐based phosphanes have recently been shown to be interesting ligands in organometallic catalysis. The synthesis of novel [2.2]paracyclophane‐substituted triazole‐based phosphane ligands was achieved. The possibility to synthesize these molecules in a highly enantioenriched form is also reported. Moreover, the ability of the novel ligands to coordinate with metal centers was explored. Besides a dinuclear copper complex, a PdII complex could also be isolated, the structure of which was characterized by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Previously, our group has shown that combinations of [CpRu(CH 3 CN) 3 ][PF 6 ] 1 (10 mol%) and enantiopure pyridine monooxazoline ligands can be efficient for the stereocontrol of such transformations 13dg. Using pymox L1 in particular, decarboxylative allylic substitution of allyl aryl carbonates gave, for instance, relatively high enantiomeric excesses and regioselectivity (up to 87% ee and b:l>95:5, Scheme ) 13g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our group has shown that combinations of [CpRu(CH 3 CN) 3 ][PF 6 ] 1 (10 mol%) and enantiopure pyridine monooxazoline ligands can be efficient for the stereocontrol of such transformations 13dg. Using pymox L1 in particular, decarboxylative allylic substitution of allyl aryl carbonates gave, for instance, relatively high enantiomeric excesses and regioselectivity (up to 87% ee and b:l>95:5, Scheme ) 13g.…”
Section: Methodsmentioning
confidence: 99%
“…80% ee ). This is explained by the better leaving group ability of the corresponding nitro‐phenoxide leading to a faster isomerization and racemization 13d. On the other hand, substitutions on the cinnamyl part of electron‐withdrawing groups led to good selectivity levels but lower conversions (entries 6 and 7).…”
Section: Methodsmentioning
confidence: 99%
“…Thus we assume 1 crystallizes as racemic conglomerate . It is worth noting that due to an efficient methodology for the resolution of racemic formyl[2.2]paracyclophane, the phosphine L1 can be obtained in a highly enantioenriched form, which enables a straightforward synthesis of an enantioenriched gold complex.…”
Section: Resultsmentioning
confidence: 99%
“…Elemental analyses were carried out with an ElementarVario EL or Micro Cube. [AuCl(tht)], [AuC 6 F 5 (tht)], as well as the employed ligands L1 and L2 and complex 4 were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation